Experimental and numerical optimization study of shock wave damping in aluminum panel sandwich (Fracture and Structural Integrity, 2020)
Sandwich panels with polymer composite and light core composites are widely used in aircraft and spacecraft, vessels, trains, submarines, and cars. Due to their high strength to weight ratio, high stability, and high corrosion resistance, these structures have become particularly important in the industry. Reduction in impact energy, shock waves, and noise in many industries, including the automotive and military industries. Porous materials have always been the focus of attention due to their shock-reducing effects in various protective applications. For this reason, the study of physics governing shock propagation problems in porous media is of particular importance, and the complexity of the governing equations also results in the numerical solution of these equations with many computational problems and costs. In this paper, shock wave damping is investigated numerically and experimentally in aluminum blocks with porous grains scattered inside aluminum. The deformations of the specimens in numerical simulation and experimental testing have been compared. The results show that this material behaves similarly to the aluminum foam in both static loadings (practical pressure testing) and dynamic loading (explosion simulation) results, again similar to aluminum foam.
Keywords: Sandwich Panel; Shock Wave; Blast; Aluminum Foam; Porous material